SYMBOLIC CULTURAL VALUE: CREATIVITY AND COUNTERPRODUCTIVITY IN CITAYAM FASHION WEEK 2022 IN INDONESIA - Noorzeha, Fuad; Sutono, Agus; Abraham Ziswan Suryosumunar, John (UI Scholars Hub, 2024)
The phenomenon of Citayam Fashion Week has symbolically influenced the way lower-class youth dress in central Jakarta. What was once an urban area in Sudirman has transformed into a fashion arena after videos of young people sporting distinctive clothing styles went viral. More than just a social gathering, this occurrence has attracted significant attention on social media, showcasing unique fashion expressions. However, this spontaneous and instantaneous trend has sparked a wide range of responses, with opinions varying from viewing it as a creative expression to considering it counterproductive. This study employs Jean Baudrillard’s theory as its formal framework in qualitative analysis, with Citayam Fashion Week serving as the material object of inquiry. The findings reveal the symbolic imagery that influences societal perceptions through creative fashion expressions and highlights the potential negative impacts on society, particularly among contemporary youth.